The Impact of Obediance Pressure on Risky Choice Behavior - Hariri Hariri; Muhammad Basalamah (JAFFA, 2019)
This research aims at analyzing the determinance of financial statement fraud using MCP Theory (Motives, Capability, and Possibility). Motives variable used the proxy of leverage ratio (LEV), capability variable used the proxy by calculating the total number of board of directors and possibility variable used the proxy of the proportion of total audit committee. The criteria for sample in this research were companies with special notation or 'tattoo' from IDX from 2016 through 2018 amounted to 30 companies. The data analysis method used the SPSS. The results of the research show that Motives, Capability and Possibility variables simultaneously affect the financial statement fraud significantly and positively.